2013
DOI: 10.1111/jcmm.12021
|View full text |Cite
|
Sign up to set email alerts
|

Structural and ultrastructural evidence for telocytes in prostate stroma

Abstract: The prostate comprises a glandular epithelium embedded within a fibromuscular stroma. The stroma is a complex arrangement of cells and extracellular matrix (ECM) components in addition to growth factors, regulatory molecules, remodelling enzymes, blood vessels, nerves and immune cells. The principal sources of ECM components are fibroblasts and smooth muscle cells (SMC), which synthesize the structural and regulatory components of the ECM. Telocytes (TCs) were recently described as a novel stromal cell type th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
68
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 81 publications
(71 citation statements)
references
References 48 publications
3
68
0
Order By: Relevance
“…The interalveolar region contained predominantly CD34‐positive cells on P30, with the formation of networks that separate the clusters of alveoli from each other and separate clusters of alveoli from the periurethral smooth muscle, thus attributing to the exclusively CD34‐positive interstitial cells uniquely a role of ICCs progenitor cells is a limited proposition, in view of the evidence that these cells possess many other functions in the tissue organisation and functionality in various organs 8, 10, 11, 12, 17, 18, 24, 25. CD34‐positive telocytes that do not express c‐Kit may also perform a pacemaker function 48, 49 via c‐Kit‐independent pathways, such as the SK3 pathway, by inhibiting electrical activity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The interalveolar region contained predominantly CD34‐positive cells on P30, with the formation of networks that separate the clusters of alveoli from each other and separate clusters of alveoli from the periurethral smooth muscle, thus attributing to the exclusively CD34‐positive interstitial cells uniquely a role of ICCs progenitor cells is a limited proposition, in view of the evidence that these cells possess many other functions in the tissue organisation and functionality in various organs 8, 10, 11, 12, 17, 18, 24, 25. CD34‐positive telocytes that do not express c‐Kit may also perform a pacemaker function 48, 49 via c‐Kit‐independent pathways, such as the SK3 pathway, by inhibiting electrical activity.…”
Section: Discussionmentioning
confidence: 99%
“…Telepodes can be divided into dilated portions, podoms and fibrillar‐like sections called podomers 8, 9. Several functions of telocytes have been proposed, which vary from organ to organ, such as organisation of the stroma through modulation of intercellular communication 15, regeneration of cardiac muscle 10, immune response in the duodenum 11, contractility of the uterus 12 and in intercellular electrical communication 18, among others.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Telocytes are closely related with pancreatic acinar cells ; Nico- and are located beneath prostate gland epithelium [Corradi et al, 2013], gastric and intestinal glands [Vannucchi et al, 2013], conjunctival epithelium, and pigmentary cells of the retina [Luesma et al, 2013]. Telopode-epithelial contacts were documented in the hen uterine tube [Gandahi et al, 2012].…”
Section: Discussionmentioning
confidence: 99%
“…Many investigations have documented that TCs and their Tps are resident in various organs of many mammals, including human, pig, gerbil, mouse, rat and degus 1, 2, 3, 4, 5. Studies on TCs and Tps have also been reported in lower animals, such as newts, zebrafish and turtles 6, 7.…”
mentioning
confidence: 99%